Battle of the Retail Channels: How Product Selection and Geography Drive Cross-Channel Competition - Brynjolfsson, Erik; Hu, Yu (Jeffrey); Rahman, Mohammad S. (Management Science, 2009)
A key question for Internet commerce is the nature of competition with traditional brick-and-mortar retailers. Although traditional retailers vastly outsell Internet retailers in most product categories, research on Internet retailing has largely neglected this fundamental dimension of competition. Is cross-channel competition significant, and if so, how and where can Internet retailers win this battle? This paper attempts to answer these questions using a unique combination of data sets. We collect data on local market structures for traditional retailers, and then match these data to a data set on consumer demand via two direct channels: Internet and catalog. Our analyses show that Internet retailers face significant competition from brick-and-mortar retailers when selling mainstream products, but are virtually immune from competition when selling niche products. Furthermore, because the Internet channel sells proportionately more niche products than the catalog channel, the competition between the Internet channel and local stores is less intense than the competition between the catalog channel and local stores. The methods we introduce can be used to analyze cross-channel competition in other product categories, and suggest that managers need to take into account the types of products they sell when assessing competitive strategies.